Impact des laisses végétales sur la dynamique des plages sableuses, Martinique, Petites Antilles - Franck Dolique; Mouncef Sédrati; Quentin Josso (VertigO)
The beaches of the Caribbean Islands are regularly affected by the stranding of plant debris (algae, phanerogams, etc.) at the tide mark line, which becomes mixed with sand at the top of the beach, along with deadwood and other waste of anthropogenic origin. This situation has worsened since 2011 as a result of the stranding of sargassum seaweed, which significantly reduces beach access and produces emanations of harmful gases. This is damaging for the Caribbean islands of the Lesser Antilles, since their economies are heavily dependant on tourism. These deposits also play a complex role in the sedimentary dynamics of beaches by favouring the trapping or, alternatively, the re-mobilization of sands. Does this accumulation of drift reinforce the erosion of beaches or, on the contrary, does it contribute to their growth? What are the impacts of the manual or mechanical collection of these drift materials on the sediment budget and dynamics of beaches? In an attempt to address these questions, an in-situ experimental study was carried out on the beaches of the Anse Caffard (Le Diamant) and the Anse au Bois (Sainte-Anne) on Martinique. The pocket beach of the Anse au Bois was divided into three sectors. In the first sector, the drift was completely removed by collection, while a second sector was treated by spreading the stranded debris and a third sector was left in a natural state, without any collection. Topographic and hydrodynamic measurements were carried out on the three sectors to characterize the sedimentary response of the beach according to these three methods of managing the stranded drift. Measurements were also carried out on the Anse Caffard beach, which was managed by mechanical collection. These experiments reveal morphodynamic trends which need to be taken into account in the framework of the management of sargassum seaweed crises.